2021
DOI: 10.1186/s40168-021-01016-x
|View full text |Cite
|
Sign up to set email alerts
|

Revealing taxon-specific heavy metal-resistance mechanisms in denitrifying phosphorus removal sludge using genome-centric metaproteomics

Abstract: Background Denitrifying phosphorus removal sludge (DPRS) is widely adopted for nitrogen and phosphorus removal in wastewater treatment but faces threats from heavy metals. However, a lack of understanding of the taxon-specific heavy metal-resistance mechanisms hinders the targeted optimization of DPRS’s robustness in nutrient removal. Results We obtained 403 high- or medium-quality metagenome-assembled genomes from DPRS treated by elevating cadmium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 88 publications
(116 reference statements)
1
15
0
Order By: Relevance
“…Genome-centric metagenomics can unravel microbes’ metabolic potentials at species resolution. , Coupling the taxon-specific functional information of microbes and molecular traits of DOM provides the opportunity to correlate DOM molecules with microbial phylogeny and functionality. Besides, Yu et al recently introduced reactomics, which evaluates untargeted MS profiles at the reaction level.…”
Section: Introductionmentioning
confidence: 99%
“…Genome-centric metagenomics can unravel microbes’ metabolic potentials at species resolution. , Coupling the taxon-specific functional information of microbes and molecular traits of DOM provides the opportunity to correlate DOM molecules with microbial phylogeny and functionality. Besides, Yu et al recently introduced reactomics, which evaluates untargeted MS profiles at the reaction level.…”
Section: Introductionmentioning
confidence: 99%
“…The microbiota acquire resistance with cumulative metal concentration thresholds irrespective of their essentiality or non-essentiality to the environment. Here, the metal speciation suggested that 75% of the reconstructed MAGs were showing resistance to Cr, Co, Zn, Cd, As, Cu and have evolved to tolerate heavy metal concentrations using various processes includes biosorption, intra/extracellular entrapment and transportation across cell membrane which form the basis of different bioremediation strategies (Ahemad, 2012, Nanda et al ., 2019, Lin et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The genome taxonomy database (GTDB) uses a set of conserved proteins to normalize taxonomic ranks based on relative evolutionary divergence with the aim to provide an objective, phylogenetically consistent classification of prokaryotes [65,[69][70][71]. The Genome Taxonomy Database Toolkit (GTDB-Tk) furthermore enables to efficiently classify bacterial and archaeal draft genome assemblies [70,72,73]. However, in metagenomics, the clustering and binning of contigs into individual genomes commonly results in a substantial number of unbinned fractions [77,78].…”
Section: A Deep Comparative Metaproteomic Study On the Core Microbiom...mentioning
confidence: 99%
“…The Genome Taxonomy Database Toolkit (GTDB-Tk) supports the classification of draft bacterial and archaeal genomes [70]. However, this tool was developed for genome assemblies or metagenome-assembled genomes that are constructed by clustering related contigs into bins [72, 73]. The binning procedure, however, leaves for complex metagenomes usually a substantial fraction of unbinned sequences [59].…”
Section: Introductionmentioning
confidence: 99%